(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The research aims to reveal the level of visual thinking skills among students of the Department of Physics and its relationship to the trend towards e-learning. By testing the visual thinking and the measure of attitude towards e-learning and after verifying the psychometric properties of both tools, they were applied to 100 male and female students from the research sample. The results showed a decrease in the level of visual thinking skills among students of the Department of Physics with positive attitudes towards e-learning and the absence of a correlation between visual thinking skills and the trend towards e-learning. In light of the research results, the study came out with some recommendations and suggestions.